nCoV-19 therapeutics using cucurbitacin I structural derivatives: an in silico approach - Ram Lal Swagat Shrestha; Bishnu Prasad Marasini; Jhashanath Adhikari Subin (SpringerOpen, 2024)
Abstract Background Cucurbitacins are present in some common vegetables as secondary metabolites and are used by the plants against harmful microbes. Exploration of this capability of natural product based substances against wide variety of microbes seems relevant due to the ease of availability of the resources and safety. In this regard, considering the current pandemic, the antiviral properties of these molecules with a subset of Cucurbitacin I structural derivatives have been screened. The inhibition potential of the phytochemicals was assessed by the stability of the protein-ligand complex formed with the nucleocapsid protein (PDB ID: 7CDZ) of SARS-CoV-2 by computational methods. The proposition of an alternate antiviral candidate that is cost-effective and efficient relative to existing formulations is the main objective of this work. Results Server-based molecular docking experiments revealed CBN19 (PubChem CID: 125125068) as a hit candidate among 101 test compounds, a reference molecule (K31), and 5 FDA-approved drugs in terms of binding affinities sorted out based on total energies. The molecular dynamics simulations (MDS) showed moderate stability of the protein-CBN19 complex as implied by various geometrical parameters RMSD, Rg, RMSF, SASA and hydrogen bond count. The ligand RMSD of 3.0 ± 0.5 Å, RMSF of Cα of protein with less than 5 Å, and smooth nature of SASA and Rg curves were calculated for the adduct. The binding free energy (− 47.19 ± 6.24 kcal/mol) extracted from the MDS trajectory using the MMGBSA method indicated spontaneity of the reaction between CBN19 and the protein. The multiple ADMET studies of the phytochemicals predicted some drug-like properties with minimal toxicity that mandate experimental verification. Conclusions Based on all the preliminary in silico results, Cucurbitacin, CBN19 could be proposed as a potential inhibitor of nucleocapsid protein theoretically capable of curing the disease. The proposed molecule is recommended for further in vitro and in vivo trials in the quest to develop effective and alternate therapeutics from plant-based resources against COVID-19.